(untitled) (World Economics and Finance Bulletin, 2023)
This article explores the essence of the concept of "financial resources of an enterprise" at the macro and micro levels, improves their definition as an economic category. The components and structure of sources of financial resources are determined, the expediency of their use is justified. The purpose of the article is to study essence of the concept and composition of financial resources of the enterprise, as well as the study of problems associated with their formation